CLINICAL ANALYSIS OF C-REACTIVE PROTEIN AS AN INFLAMMATORY MARKER IN CHRONIC KIDNEY DISEASE (Pakistan Journal of Medical & Cardiological Review, 2026)
Chronic kidney disease (CKD) is a progressive condition associated with significant morbidity and mortality worldwide, largely driven by persistent inflammation and impaired renal function. This study aimed to assess inflammatory and renal biomarkers, particularly high-sensitivity C-reactive protein (hs-CRP), in patients with CKD and evaluate their association with disease severity. A cross-sectional analytical study was conducted on 100 CKD patients in a tertiary care hospital. Demographic and clinical data were recorded, and biochemical parameters including hs-CRP, serum creatinine, estimated glomerular filtration rate (eGFR), serum albumin, and urinary albumin-to-creatinine ratio (UACR) were analyzed using standard laboratory techniques. The results showed that the mean age of participants was 52.26 ± 16.38 years, with a slightly higher proportion of males (56%). Elevated hs-CRP levels (10.92 ± 4.93 mg/L) indicated a high inflammatory burden among CKD patients. Serum creatinine (5.09 ± 2.46 mg/dL) and UACR (528.75 ± 253.19 mg/g) were markedly increased, while eGFR values showed wide variability, reflecting impaired renal function. Statistical analysis revealed significant differences among study variables (F(5, 594) = 238.49, p < .001), confirming a strong association between inflammation and renal dysfunction. In conclusion, elevated hs-CRP levels are strongly associated with systemic inflammation and disease progression in CKD patients. hs-CRP serves as a reliable, cost-effective biomarker for monitoring inflammation and identifying high-risk individuals. Routine assessment of CRP alongside renal function markers may enhance early diagnosis, improve clinical management, and reduce CKD-related complications.